Epigenetics in Glaucoma - Fabiana D’Esposito; Caterina Gagliano; Philip Anthony Bloom; Maria Francesca Cordeiro; Alessandro Avitabile; Giuseppe Gagliano; Ciro Costagliola; Teresio Avitabile; Mutali Musa; Marco Zeppieri (Medicina, 2024)
Primary open angle glaucoma (POAG) is defined as a “genetically complex trait”, where modifying factors act on a genetic predisposing background. For the majority of glaucomatous conditions, DNA variants are not sufficient to explain pathogenesis. Some genes are clearly underlying the more “Mendelian” forms, while a growing number of related polymorphisms in other genes have been identified in recent years. Environmental, dietary, or biological factors are known to influence the development of the condition, but interactions between these factors and the genetic background are poorly understood. Several studies conducted in recent years have led to evidence that epigenetics, that is, changes in the pattern of gene expression without any changes in the DNA sequence, appear to be the missing link. Different epigenetic mechanisms have been proven to lead to glaucomatous changes in the eye, principally DNA methylation, post-translational histone modification, and RNA-associated gene regulation by non-coding RNAs. The aim of this work is to define the principal epigenetic actors in glaucoma pathogenesis. The identification of such mechanisms could potentially lead to new perspectives on therapeutic strategies.